The Lived Experiences of Mothers of Children with Disabilities. Issue 4 (2nd October 2019) - Munsell, Sonya E.; O'Malley, Lori
ABSTRACT: The purpose of this research study was to explore the lived experiences of parents of children with disabilities. More specifically, this study aimed to give voice to these parents by encouraging them to be active participants in the research process. The researchers used the Photovoice technique as a way for participants to explore their experiences. Participants were given a list of questions related to raising a child with a disability. Participants (all of whom were mothers) responded to these questions by taking photos. Upon completion of the photo-taking process, each mother participated in a one-on-one semistructured interview with the researchers. Additionally, mothers completed a short demographic survey. The researchers used the SHOWeD method as a springboard for discussing the photos and the meanings behind the photos. Open coding led to the establishment of three broad themes: individuation, sensitivity, and advocacy. Mothers acknowledged that, although raising a child with a disability could be hard work, it was also accompanied by a number of rewarding and joyful experiences.